Smartphone Control Mobile Robot for Education and Research - Onyinye Ikpeze; Temitayo Ejidokun; Moses Onibonoje (Journal of Robotics)
In this digital age there is a growing interest in robotics by students in basically all age grades beginning from the toy robot cars used by preschoolers, to hi-tech robots used by teenagers and youths such as Sphero BOLT, Grillbot, and many others available in the market. In other to spark interest of youngsters in science, technology, engineering, and math (STEM) fields and also for robotics enthusiasts without making learning complex but simple and intuitive this cost-effective mobile robot called IKPEZE Robot was designed and developed. This can be used for education and research purposes in laboratories; knowledge gathered from this approach can also be applied to wider ranges of robotics. IKPEZE Robots has an added vision and audio capability, which provides surveillance of its immediate environment. Our main goal was to develop a low-cost mobile robot, which is cheaper than most commercial robots sold today and can find application not only in education and research, but also in other applications. This mobile robot was developed by designing and implementing a chassis having a Raspberry Pi controller programmed in C language in a Debian Linux-based OS that was used to control the chassis remotely via a Wi-Fi network. A mobile application was loaded into an Android smartphone with an easy-to-use graphical user Interface (GUI). Captured footages are sent wirelessly via Wi-Fi to the Android smartphone and it is stored in the local memory of the smartphone.